Food policy in 2017-2018: Progress, uncertainty, and rising antiglobalism - Fan, Shenggen (International Food Policy Research Institute, 2018)
The year 2017 was marked by increasing uncertainty amid mixed signs of progress. The world enjoyed a strong economic recovery following a period of stagnation, but global hunger increased as conflicts, famine, and refugee crises persisted. The global landscape continued to change, as antiglobalization sentiment threatened international trade and investment as well as the flow of people and knowledge. Major global events evidenced a shift away from the decades-long trend toward greater global integratio. These events included the failure to reach agreement at the World Trade Organization (WTO) Ministerial Conference as well as bilateral actions of the United States and the United Kingdom, all signaling the potential rise of isolationism and protectionism. These changes create uncertainties for global food security and nutrition.